2018
DOI: 10.1097/tp.0000000000001917
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Airway Fibrosis in Orthotopic Mouse Lung Transplantation Models—An Experimental Reappraisal

Abstract: BACKGROUND: Several mouse lung transplantation (Tx) models have been proposed for the study of chronic airway fibrosis (CAF), the most prevalent complication seen in human lung transplant recipients, termed chronic lung allograft dysfunction (CLAD). Alternatively, it has been called for to establish an experimental animal model for restrictive allograft syndrome (RAS), another phenotype of CLAD. However, these mouse transplant models exhibit significant heterogeneity in consistency and reproducibility. We ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 38 publications
3
6
2
Order By: Relevance
“…21,22,25,[34][35][36][37][38] We have found that fibrosis diminishes over time with surgical experience, and currently we observe minimal fibrosis in allografts not subjected to IRI, in contrast to our earlier data. Allograft fibrosis in the B10→B6 LT model is highly variable among different surgeons and research groups, whereas AR is mild but reproducible.…”
Section: Cold and Warm Ischemic Preservation Augment Allograft Fibrcontrasting
confidence: 89%
See 3 more Smart Citations
“…21,22,25,[34][35][36][37][38] We have found that fibrosis diminishes over time with surgical experience, and currently we observe minimal fibrosis in allografts not subjected to IRI, in contrast to our earlier data. Allograft fibrosis in the B10→B6 LT model is highly variable among different surgeons and research groups, whereas AR is mild but reproducible.…”
Section: Cold and Warm Ischemic Preservation Augment Allograft Fibrcontrasting
confidence: 89%
“…Allograft fibrosis in the B10→B6 LT model is highly variable among different surgeons and research groups, whereas AR is mild but reproducible. 21,22,25,[34][35][36][37][38] We have found that fibrosis diminishes over time with surgical experience, and currently we observe minimal fibrosis in allografts not subjected to IRI, in contrast to our earlier data. 20 We therefore hypothesized that the limited fibrotic WIT nor 30 minutes CIT plus 60 minutes WIT caused CR (not shown).…”
Section: Cold and Warm Ischemic Preservation Augment Allograft Fibrcontrasting
confidence: 89%
See 2 more Smart Citations
“…While the relative contributions of CD4+ and CD8+ T cell subsets to rejection are unclear, the CD4+ alloimmune response is typically short‐lived due to the destruction of donor antigen‐presenting cells (APCs) post‐transplantation . The principal alloimmune response therefore appears to be largely mediated by CD8+ CTLs, although this response may vary according to the transplant model and species . In our study, both CD4+ and CD8+ seemingly play a role in the rejection process on day 3; the CD4+ signal declines on day 7; however, the CD8+ signal doubles, suggesting that the CD8+ T‐cell response is the principal mediator of rejection (Figures and ).…”
Section: Discussionmentioning
confidence: 67%